2016
DOI: 10.1016/j.dadm.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The clinical, neuroanatomical, and neuropathologic phenotype of TBK1‐associated frontotemporal dementia: A longitudinal case report

Abstract: IntroductionMutations in the TANK-binding kinase 1 (TBK1) gene have recently been shown to cause frontotemporal dementia (FTD). However, the phenotype of TBK1-associated FTD is currently unclear.MethodsWe performed a single case longitudinal study of a patient who was subsequently found to have a novel A705fs mutation in the TBK1 gene. He was assessed annually over a 7-year period with a series of clinical, cognitive, and magnetic resonance imaging assessments. His brain underwent pathological examination at p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 17 publications
2
33
0
Order By: Relevance
“…715/2984 samples that were analysed with the NGS gene-panel were also exome sequenced (see Methods), which allowed discovery of only two additional mutations classified as DVs, in TBK1 ( 25 ) , and DNMT1 (26), and no DVs in other neurology-relevant genes not included in the panel.…”
Section: Resultsmentioning
confidence: 99%
“…715/2984 samples that were analysed with the NGS gene-panel were also exome sequenced (see Methods), which allowed discovery of only two additional mutations classified as DVs, in TBK1 ( 25 ) , and DNMT1 (26), and no DVs in other neurology-relevant genes not included in the panel.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in many other genes, often initially discovered as uncommon causes of ALS, have subsequently been identified in patients with FTD ± ALS. Although reports on the associated neuropathology are still rare, TDP‐43 pathology has been described in cases with mutations in genes encoding TANK‐binding kinase 1 ( TBK1 ) , sequestosome 1 , ubiquilin 2 , optineurin and dynactin . Current information is insufficient to know if any of these mutations is associated with a unique pathological signature; however, in the case of TBK1 mutations, the associated pattern of TDP‐43 pathology is reported to be inconsistent (FTLD‐TDP type A or B) with unusual presence of numerous TDP‐43‐positive neuritic structures at the cerebral cortex/subcortical white matter junction reported in one case .…”
Section: Ftld‐tdpmentioning
confidence: 99%
“…Genetic studies of TBK1 have identified nonsense, frameshift, missense and deletion mutations in both sporadic and familial ALS, FTD and ALS/FTD, which predominately results in the loss-of-function phenotypes that reduce levels or activity of the kinase and pathological TDP-43 inclusions (45,66). Loss of TBK1 function in these diseases impacts multiple protein-protein interactions and cellular pathways including autophagy and inflammation (29,40).…”
Section: Discussionmentioning
confidence: 99%